2018
DOI: 10.1016/j.ygeno.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term affected flat oyster (Ostrea edulis) haemocytes show differential gene expression profiles from naïve oysters in response to Bonamia ostreae

Abstract: European flat oyster (Ostrea edulis) production has suffered a severe decline due to bonamiosis. The responsible parasite enters in oyster haemocytes, causing an acute inflammatory response frequently leading to death. We used an immune-enriched oligo-microarray to understand the haemocyte response to Bonamia ostreae by comparing expression profiles between naïve (NS) and long-term affected (AS) populations along a time series (1 d, 30 d, 90 d). AS showed a much higher response just after challenge, which migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 85 publications
0
42
0
Order By: Relevance
“…Because of the remote location combined with reduced water inflow and currents, pathogens and competitors like Bonamia ostreae and Magallana gigas appeared in the Limfjord later than at other locations in Europe 42,43 . Another hypothesis is based on the results of Ronza et al 44 : they showed that O. edulis has not developed any resistance to bonamiosis in the Limfjord yet. The presence of B. ostreae in the North Sea may therefore be a reason why the native oyster has not recolonized the Wadden Sea again 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the remote location combined with reduced water inflow and currents, pathogens and competitors like Bonamia ostreae and Magallana gigas appeared in the Limfjord later than at other locations in Europe 42,43 . Another hypothesis is based on the results of Ronza et al 44 : they showed that O. edulis has not developed any resistance to bonamiosis in the Limfjord yet. The presence of B. ostreae in the North Sea may therefore be a reason why the native oyster has not recolonized the Wadden Sea again 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is based on the results of Ronza et al 44 : they showed that O. edulis has not developed any resistance to bonamiosis in the Limfjord yet. The presence of B. ostreae in the North Sea may therefore be a reason why the native oyster has not recolonized the Wadden Sea again 44 . In the past, it has been observed that B. ostreae was eliminated during cold winters, while O. edulis was able to survive 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have applied genetic and genomic tools to study O. edulis in the absence of a reference genome assembly. Such work has been strongly targeted towards understanding bonamiosis, either by identifying candidate quantitative trait loci (QTL) and genetic outliers linked to Bonamia resistance (Lallias et al, 2009; Harrang et al, 2015; Vera et al, 2019) or by studying gene expression responses to Bonamia infection (Pardo et al, 2016; Ronza et al, 2018). SNP genotyping arrays with low (Lapègue et al, 2014) and medium (Gutierrez et al, 2017) density have also been developed for genetics applications.…”
Section: Introductionmentioning
confidence: 99%
“…While interspecific transcriptomic comparisons can be quite powerful (Evans, 2015), designs targeting intraspecific differences can also be used to address key questions in wildlife disease. These investigations are particularly informative when they contrast populations with varying historical pathogen exposure regimes: persistent exposure may drive divergence in gene expression, including gene regulation differences associated with the evolution of host resistance, which population‐level gene expression assays can dissect (Bonneaud et al, 2012; Campbell et al, 2018; Grogan, Cashins, et al, 2018; Ronza et al, 2018). Such approaches have been used to identify genes in exposed populations that are potential targets of selection for host resistance, even when the history of exposure is relatively brief in an evolutionary sense (i.e., decades).…”
Section: Synthesizing Current Insights On Host Gene Expression Respon...mentioning
confidence: 99%